HIV preintegration complexes - Ratner, Lee (Henry Stewart Talks, 2007)
Role of cell cycle progression in retrovirus replication, Resting T-cells and HIV, Uncoating and PIC nuclear import, Preintegration complex (PIC), Intracellular transport of PIC, HIV-1 Vpr vs. HIV-2 Vpx, HIV-1 Vpr interaction factors, HIV-2: model system for PIC nuclear import, Vpx cellular localization, Ability of Vpx-NLS mutant viruses to infect arrested and dividing U937 cells, Nuclear localization signal of HIV-2 Vpx, Vpx interaction with HSP 40, Heat shock proteins and viruses, Over-expression of DNAJB6 causes reduction of Vpx packaging in VLP, Down regulation of DNAJB6 reduces nuclear import of HIV-2 PIC, Novel mechanism of Vpx-mediated PIC import
Archived at 2018/12/10